Implications of Islamic Law on Credit-Based Sales in Reducing Social and Economic Inequalities in Society - Siti Ropiah (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2025)
This study investigates the contribution of Islamic legal principles to the regulation of credit-based sales and their potential in mitigating social and economic inequalities. By focusing on Shariah-compliant financing models—particularly murabahah and ijarah—the research highlights how Islamic jurisprudence offers a distinctive framework for promoting economic inclusivity among low-income communities. The analysis centres on the extent to which principles of distributive justice, ethical accountability, and economic sustainability are embedded within the practical operations of Islamic financial institutions. Employing a qualitative methodology rooted in both normative and empirical legal inquiry, the study reveals that Islamic credit-based sales, when aligned with foundational legal-ethical values such as maslahah (public interest) and transparency, contribute significantly to narrowing structural disparities. Nonetheless, the study also identifies critical implementation gaps, including inconsistencies in regulatory oversight and challenges in maintaining fidelity to core Islamic legal norms. The research contributes to contemporary discourses in Islamic economics and legal reform by offering a nuanced understanding of how Islamic credit systems can be mobilised as tools for socioeconomic justice. It calls for enhanced institutional frameworks that ensure these financial instruments not only comply with Shariah standards but also realise their transformative potential in addressing inequality